Design for Visually Impaired People Based on Their Functional and Emotional Requirements (Journal of Fiber Bioengineering and Informatics, 2024)
Human beings depend on vision to obtain external information from their surroundings. It is, therefore,difficult for visually impaired people to perceive visual sensations in their daily lives. Currently, thereare many related designs for the convenience of visually impaired people in urban construction anddaily use. Still, little research has been done on their clothing design, especially designs that combinetheir functional and emotional requirements. In this study, interviews were conducted to examine thedifficulties visually impaired people face in dressing and their functional and emotional requirements forclothing. Based on the design investigation of visually impaired people and the interview survey on theirrequirements for clothing, this study also explored the application of the sensory compensation designconcept (mainly tactile compensation) in clothing design. As a result, four clothing styles were designedto meet their physical and psychological needs. It is hoped that the study will provide a way of thinkingabout clothing design for visually impaired people and call for more attention and help.